2020
DOI: 10.1007/s11906-020-01120-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Management in Acute Ischemic Stroke

Abstract: Purpose of Review Abrupt blood pressure (BP) rise is the most common clinical symptom of acute ischemic stroke (AIS). However, BP alterations during AIS reflect many diverse mechanisms, both stroke-related and nonspecific epiphenomena, which change over time and across patients. While extremes of BP as well as high BP variability have been related with worse outcomes in observational studies, optimal BP management after AIS remains challenging. Recent Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 129 publications
2
26
0
1
Order By: Relevance
“…Targeting systemic haemodynamics alone is also not a promising strategy (also previously shown in a meta-analyse of blood pressure lowering agents by Sandset et al [16]) and appears even to have detrimental effects (found in 5/21 trials and shown in a sub-group analyse of the INWEST trial [167]). However, the link between blood pressure changes and clinical outcome in AIS patients is extremity complex and optimal blood pressure management remains challenging since it depends on treatment strategy, local vascular function and especially the degree of reperfusion or persistent occlusion (reviewed by Gasecki et al [168]). Only for one highly investigated compound, Nimodipine, 3 out of 10 trials showed a beneficial effect when given within 24 h of stroke onset.…”
Section: Categorical Drug Effectsmentioning
confidence: 99%
“…Targeting systemic haemodynamics alone is also not a promising strategy (also previously shown in a meta-analyse of blood pressure lowering agents by Sandset et al [16]) and appears even to have detrimental effects (found in 5/21 trials and shown in a sub-group analyse of the INWEST trial [167]). However, the link between blood pressure changes and clinical outcome in AIS patients is extremity complex and optimal blood pressure management remains challenging since it depends on treatment strategy, local vascular function and especially the degree of reperfusion or persistent occlusion (reviewed by Gasecki et al [168]). Only for one highly investigated compound, Nimodipine, 3 out of 10 trials showed a beneficial effect when given within 24 h of stroke onset.…”
Section: Categorical Drug Effectsmentioning
confidence: 99%
“…Stroke, one of the leading causes of death worldwide, is caused by the sudden blockage of blood flow or the rupture of blood vessels and can be divided into ischemic stroke and hemorrhagic stroke (Herpich and Rincon 2020;Shao et al 2020;Stinear et al 2020). Ischemic stroke accounts for approximately 70-85% of all strokes worldwide (Gąsecki et al 2020). After cerebral ischemia, intravenous thrombolysis in glucose-free DMEM solution at 37 °C for 0, 2, 4, 6, or 8 h, as previously described (Lai et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke has been recognised as the leading cause of mortality and disability worldwide (Chen et al, 2019), and most cases (75%–80%) are due to ischaemic stroke (Gąsecki et al, 2020). It occurs when a blood clot (either a thrombus or an embolus) causes a significant reduction in blood flow to the brain (Bamford et al, 1991; Hossmann & Schuier, 1980), resulting in irreversible damage to neurons and glia.…”
Section: Introductionmentioning
confidence: 99%
“…The hypoperfused peri‐ischaemic region is characterised by the presence of electrophysiologically inactive, but still at least partially metabolically active neurons (González, 2006; Leigh et al, 2018). If blood flow is restored as soon as possible, the viability and function of cells in the peri‐ischaemic region can be salvaged; therefore, it has recently become the focus of numerous studies (Gąsecki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%